Unidade de ensino potencialmente significativa: uma proposta no estudo de gráficos em cinemática para o 9º ano do ensino fundamental - Beserra, Francisca Daniele Costa de Lima (2020)
Faced with the traditional teaching model prevalent in schools today, teachers are unprepared to innovate in the approach to physics content and end up opting for the classic way of teaching that attracts little students. With the intention of collaborating with the development of new didactic strategies that promote the improvement of physics teaching, this work carried out within the scope of the National Professional Master in Physics Teaching brings the proposal to elaborate, apply and evaluate the potentialities of a Potentially Significant Teaching Unit (UEPS) idealized by Moreira, based on Ausubel's Meaningful Learning Theory. The content chosen to be worked on were the graphic representations of the hourly functions of the Uniform Rectilinear Movement and the Uniformly Varied Rectilinear Movement because we believe it is a topic treated with little relevance, mainly at the elementary school level. The pedagogical intervention to apply the sequence was carried out in six meetings between the months of March and May 2019 in a class of the 9th grade of elementary school in a public school in the city of Russas, Ceará. The first step in the implementation of the UEPS was the survey of previous knowledge through an initial questionnaire, so that the students were then introduced to the content through problem situations and collaborative and individual activities. Among the proposed activities were: the exhibition of a video, the realization of a board game and an experimental practice, all previously organized according to the sequence of application of the UEPS and always seeking progressive differentiation and integrative reconciliation. Of a qualitative nature, this research enables the collection of results centered on the observation made during the pedagogical intervention. During and after the application of this sequence, evidence of significant learning was found because the activities enabled students to overcome difficulties both in the elaboration and in the interpretation of the graphs of the hourly functions, much of this due to the proposal to rescue previous knowledge and modify the anchoring new knowledge. During and after the application of this sequence, evidence of significant learning was found because the activities enabled students to overcome difficulties both in the elaboration and in the interpretation of the graphs of the hourly functions, much of this due to the proposal to rescue previous knowledge and modify the anchoring new knowledge. The evaluation by the students was very positive, which encourages us to make future applications addressing other content